Pemberdayaan Perempuan Melalui Program Ekonomi Sirkular B3 Minyak Jelantah di Desa Kadumekar Babakancikao Purwakarta - Jalaludin Jalaludin; Syifa Nurul Luthfiyani; Muhammad Noval Al-Rasyid Mubarok (ADINDAMAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
Based on the results of observations, researchers found several phenomena related to the circular economy of used cooking oil in Kadumekar Village, one of which is that the community does not yet understand the impact of used cooking oil waste on the environment, there is still limited understanding and knowledge among the community regarding the management of used cooking oil waste, the process of utilizing used cooking oil takes a long time, and there are still very few people who know that used cooking oil has economic value. The objective of this PKM was to empower the community of Kadumekar Village, Babakancikao Subdistrict, through the empowerment of women through the B3 Waste Cooking Oil Circular Economy Program to produce soap, in order to improve the community's skills in recycling waste cooking oil. The PKM method used observation, socialization, and mentoring. The conclusion of this PKM activity shows a significant increase in the level of understanding of the partners. Before the workshop, the understanding score was in the range of 0-70 with an average of 30.5 (category of very poor understanding), but after the activity it increased to 70-90 with an average of 77 (category of good understanding). Although it did not reach 100 points because some partners were more focused on quick results without waiting for the soap drying process, which takes 24 hours to 2 weeks, this achievement is still considered very meaningful. In addition to increasing technical understanding, the PKM activity also had a positive impact in the form of awareness of the circular economy concept, the use of used cooking oil to make soap, and how to make.